Большая книга развивающих игр для настоящих мальчиков: ребусы, логические игры, головоломки, загадки / В. Г. Дмитриева ; худ.: И. Горбунова, А. Рахманов - Дмитриева Валентина Геннадьевна (Астрель, 2010)
Экземпляры: аб. ДБ (2010) / Инвентарный номер: 636 / Цена: / Сис.шифр: 99.2 / Авт.знак: Д 53 / ББК: 99.2